2021
DOI: 10.1038/s41408-021-00480-w
|View full text |Cite|
|
Sign up to set email alerts
|

Iceland screens, treats, or prevents multiple myeloma (iStopMM): a population-based screening study for monoclonal gammopathy of undetermined significance and randomized controlled trial of follow-up strategies

Abstract: Monoclonal gammopathy of undetermined significance (MGUS) precedes multiple myeloma (MM). Population-based screening for MGUS could identify candidates for early treatment in MM. Here we describe the Iceland Screens, Treats, or Prevents Multiple Myeloma study (iStopMM), the first population-based screening study for MGUS including a randomized trial of follow-up strategies. Icelandic residents born before 1976 were offered participation. Blood samples are collected alongside blood sampling in the Icelandic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 60 publications
0
62
1
3
Order By: Relevance
“…Moreover, a higher association of IMI rather than classical immunoparesis with progression is reported. Likely, the iStopMM study (NCT03327597), conducting a population-based screening for MGUS in more than 80,000 participants [57], will help to definitively define the role of the HLC assay in this patient population. In SMM, only one prospective study has been reported as suggesting a higher correlation of the risk of progression with IMI than with classical immunoparesis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a higher association of IMI rather than classical immunoparesis with progression is reported. Likely, the iStopMM study (NCT03327597), conducting a population-based screening for MGUS in more than 80,000 participants [57], will help to definitively define the role of the HLC assay in this patient population. In SMM, only one prospective study has been reported as suggesting a higher correlation of the risk of progression with IMI than with classical immunoparesis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected from 75,422 study participants (93%) between September 9, 2016 and December 31 2020 and screened for MGUS by capillary zone electrophoresis (CZE), immunofixation electrophoresis (IFE), and serum FLC assay. The iStopMM study design has previously been described in detail [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, at the present, available results are still too preliminary to achieve statistical significance. Nevertheless, two paradigmatic examples aiming to deep-screen and prevent MM by collecting high-throughput data are represented by the researches performed by Pichiorri et al [37] and within the iStopMM initiative (NCT03327597; NCT03815279) [106]. This last approach, taking advantage of a genetic screening in a population-based nationwide clinical trial with early intervention, offers the potential to collect a large biobanking repository available for future biological studies, including epigenetic profiling.…”
Section: Microrna As a New Preventive Approach To Detect The Asymptomatic To Symptomatic MM Transitionmentioning
confidence: 99%